Monoclonal anti-CD8 therapy induces disease amelioration in the K/BxN mouse model of spontaneous chronic polyarthritis - Raposo, BR (2011)
OBJECTIVE: CD8+ T cells are part of the T cell pool infiltrating the synovium in rheumatoid arthritis (RA). However, their role in the pathogenesis of RA has not been fully delineated. Using the K/BxN mouse model of spontaneous chronic arthritis, which shares many similarities with RA, we studied the potential of CD8+ T cell depletion with monoclonal antibodies (mAb) to stop and reverse the progression of experimental arthritis. METHODS: CD8+ T cells from the blood and articular infiltrate of K/BxN mice were characterized for cell surface phenotypic markers and for cytokine production. Additionally, mice were treated with specific anti-CD8 mAb (YTS105 and YTS169.4), with and without thymectomy. RESULTS: CD8+ T cells from the peripheral blood and joints of K/BxN mice were mainly CD69+ and CD62L-CD27+ T cells expressing proinflammatory cytokines (interferon-γ [IFNγ], tumor necrosis factor α [TNFα], interleukin-17a [IL-17A], and IL-4), and granzyme B. In mice receiving anti-CD8 mAb, the arthritis score improved 5 days after treatment. Recovery of the CD8+ T cells was associated with a new increase in the arthritis score after 20 days. In thymectomized and anti-CD8 mAb-treated mice, the arthritis score improved permanently. Histologic analysis showed an absence of inflammatory infiltrate in the anti-CD8 mAb-treated mice. In anti-CD8 mAb-treated mice, the serologic levels of TNFα, IFNγ, IL-6, and IL-5 normalized. The levels of the disease-related anti-glucose-6-phosphate isomerase antibodies did not change. CONCLUSION: These results indicate that synovial activated effector CD8+ T cells locally synthesize proinflammatory cytokines (IFNγ, TNFα, IL-17, IL-6) and granzyme B in the arthritic joint, thus playing a pivotal role in maintaining chronic synovitis in the K/BxN mouse model of arthritis.